Music Publications of the Beginning of 16th– 19th Centuries in Vilnius University Library - Rinkūnaitė, Aušra (Bibliotheca Lituana, 2014)
The article deals with music publications of the beginning of the 16th–19th c. – antiphonals, graduals, missals, hymnals and manuals held in the Rare Book Department of Vilnius University Library. On the basis of the extant XVIII c. manuscript catalogues of Vilnius Jesuit College Library and Library of Novitiate the publications related to music included in those catalogues are being discussed and provenances and marginalia found in them are being investigated. In addition, the article also describes anonymous manuals printed by Vilnius Academy Printing House at the end of 17th c.–18th c.: Ars et praxis musica (the first edition in 1667), Compendium regularum generalium cantus (1753) as well as canticle books in Polish and Latin languages. The second part of the article presents music activities of German composer Johann David Holland (1746–1827) who gave music lectures in Vilnius Imperial University at the beginning of the 19th c. The heritage of the Professor – nine music books – donated after his death in 1828 by his daughter Joanna to the Library of Vilnius Imperial University. The third part of the article deals with publications of church and secular music, published at the end of 16th c.–18th c., part of them – especially rare and valuable, and the diverse history of coming of these books to the Library which witnesses of their complicate and intricate journey through different institutions.